Peran Productive Engagement terhadap Kepuasan Hidup pada Lansia yang Tinggal Bersama Anak - Dewi, Mutia Aulia; Pudjiati, Sri Redatin Retno (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The phenomenon of intergenerational co-residence, particularly between older adults and their adult children, is increasingly common in Indonesia. However, not all older adults living with their children report high levels of life satisfaction. One factor that may influence life satisfaction among older adults is engagement in productive activities that provide a sense of meaning. This study aims to analyze the role of productive engagement in predicting life satisfaction among older adults living with their children. The study involved 239 older adults aged 60 and above who reside with their adult children. Life satisfaction was measured using the Satisfaction with Life Scale, and productive engagement was assessed through participation in three types of productive activities: paid work, volunteering, and caregiving for grandchildren. The results showed that, after controlling sociodemographic characteristics, productive engagement positively predicted life satisfaction among older adults living with their children. Engagement in productive activities can enhance the life satisfaction of older adults. These findings highlight the importance of supporting older adults’ participation in meaningful activities that align with their capacities, particularly within the context of intergenerational households.